Blastocystis hominis and Endolimax nana Co-Infection Resulting in Chronic Diarrhea in an Immunocompetent Male - Shah, Mitanshu (S. Karger AG, 2012)
Blastocystis hominis and Endolimax nana exist as two separate parasitic organisms; however co-infection with the two individual parasites has been well documented. Although often symptomatic in immunocompromised individuals, the pathogenicity of the organisms in immunocompetent subjects causing gastrointestinal symptoms has been debated, with studies revealing mixed results. Clinically, both B. hominis and E. nana infection may result in acute or chronic diarrhea, generalized abdominal pain, nausea, vomiting, flatulence and anorexia. We report the case of a 24-year-old immunocompetent male presenting with chronic diarrhea and abdominal pain secondary to B. hominis and E. nana treated with metronidazole, resulting in symptom resolution and eradication of the organisms. Our case illustrates that clinicians should be cognizant of both B. hominis and E. nana infection as a cause of chronic diarrhea in an immunocompetent host. Such awareness will aid in a timely diagnosis and possible parasitic eradication with resolution of gastrointestinal symptoms.